CD47 Enhances Cell Viability and Migration Ability but Inhibits Apoptosis in Endometrial Carcinoma Cells via the PI3K/Akt/mTOR Signaling Pathway - Liu, Yun; Chang, Yue; He, Xinhong; Cai, Yixuan; Jiang, Hao; Jia, Ru; Leng, Jiyan (Frontiers in Oncology, 2020)
Purposes: To measure expression levels of CD47 during endometrial carcinoma development, and to determine specific modulatory effects. Methods: CD47 expression levels in endometrial carcinoma tissues and adjacent tissues were analyzed using qRT-PCR. CD47-overexpressed or downregulated cell models were established using CD47 plasmid or CD47 shRNA. The effects of CD47 on HEC-1A and Ishikawa cell growth were evaluated using CCK-8 assays. Migration ability of transfected HEC-1A and Ishikawa cells were examined using wound healing assays. Flow cytometry was used to measure the effects of CD47 on apoptosis and the cell cycle in HEC-1A and Ishikawa cells. Western blot was used to analyze the correlation between CD47 expression level and PI3K/Akt/mTOR signaling pathway. Results: Highly expressed CD47 was observed in endometrial carcinoma tissues, with higher levels in more advanced tissues than in early tissues. Upregulation of CD47 enhanced cell viability and migration ability in HEC-1A and Ishikawa cells, while silencing CD47 caused the opposite results. CD47 overexpression suppressed apoptosis and inhibited cell cycle arrest in HEC-1A and Ishikawa cells. CD47 upregulation contributes to the activation of PI3K/Akt/mTOR signaling pathway in endometrial carcinoma cells. Conclusion: CD47 exerts oncogenic functions in endometrial carcinoma by activating PI3K/Akt/mTOR signaling, suggesting it may be a novel immunotherapeutic target for therapeutic interventions.